2014
DOI: 10.1371/journal.pone.0110899
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Task Distribution and Task Exposures among Danish House Painters: An Observational Study Combining Questionnaire Data with Biomechanical Measurements

Abstract: ObjectivesSex differences in occupational biomechanical exposures may be part of the explanation why musculoskeletal complaints and disorders tend to be more common among women than among men. We aimed to determine possible sex differences in task distribution and task-specific postures and movements of the upper extremities among Danish house painters, and to establish sex-specific task exposure matrices.MethodsTo obtain task distributions, we sent out a questionnaire to all members of the Painters' Union in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…If so, results on sex differences in the occurrence of WMSDs could be biased by inaccurate exposure assessment. In a previous study of Danish house painters,17 we found only minor sex differences in task distributions and task-specific movements and postures of the wrists. This led us to conclude that house painters in Denmark is a profession suitable for examining if women are more biologically vulnerable than men are at the assumed same level of exposure.…”
Section: Introductionmentioning
confidence: 47%
See 3 more Smart Citations
“…If so, results on sex differences in the occurrence of WMSDs could be biased by inaccurate exposure assessment. In a previous study of Danish house painters,17 we found only minor sex differences in task distributions and task-specific movements and postures of the wrists. This led us to conclude that house painters in Denmark is a profession suitable for examining if women are more biologically vulnerable than men are at the assumed same level of exposure.…”
Section: Introductionmentioning
confidence: 47%
“…If so, we think that CTS cases would probably report a higher proportion of tasks with high force requirements. Analyses comparing the sex-specific task distributions for all questionnaire responders with the subgroup of CTS cases revealed that male cases primarily did more ‘spraying’ and ‘other tasks’ and less ‘hanging wallpaper’ and had fewer pauses 17. Female cases reported more ‘full levelling’ and ‘hanging wallpaper’ and less ‘driving’.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To obtain as many technical measurements as possible, the technical measurement programme was coordinated with a corresponding technical programme in a Danish study of the wrist (goniometry),18 21 so that inclinometer and goniometer measurements were performed simultaneously. In addition to the Danish programme that covered 23 job groups, we included previous technical measurement data for 13 job groups collected by the Department of Occupational and Environmental Medicine, Lund, Sweden.…”
Section: Methodsmentioning
confidence: 99%